The machine never blinks : a graphic history of spying and surveillance - Greenberg, Ivan, 1962- (Fantagraphics Books, 2020)
"The Machine Never Blinks tells the story of surveillance and spying in history and legend from its earliest days to the present moment (from the fable of the Trojan Horse to the Patriot Act) to reveal how we have built a society in which your rights, privacy, dignity, and sanity are under constant threat. A comprehensive, eye-opening manifesto, this book will make you take a look around and wonder: Who's watching you right now?"--Publisher's Web site.